2017
DOI: 10.3390/medsci5040024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hepatitis B Viral Infection as a Predictor of Hepatic Enzymes and Compounds Alteration among Antenatal Patients

Abstract: Worldwide, hepatitis B viral (HBV) infection continues to be a major public health issue. The study was aimed at assessing HBV infection as a predictor of hepatic enzymes and compounds alteration among antenatal patients in Kano State, Nigeria. Sera were screened for HBV markers using immunochromatograhy and ELISA. Serum levels of alkaline phosphatase (ALP), asphatate aminotransferase (AST), alanine aminotransferase (ALT), albumin and bilirubin were also determined. Out of the 160 patients, 6.9% and 31.3% test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The results of the current study are in line with Abulude et al . [ 17 ] study who found that seropositive patients to HBV showed elevation of ALT, AST, and ALP activities levels.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are in line with Abulude et al . [ 17 ] study who found that seropositive patients to HBV showed elevation of ALT, AST, and ALP activities levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is well described by other authors confirming low specificity of serum albumin in differentiation between active and inactive state. 26 Serum albumin is synthesized in the liver only and therefore; a low level indicates marked hepatic impairment. 8 Our study showed that there was no association between TSB level and whether or not the patient has AH or IC.…”
Section: Discussionmentioning
confidence: 99%
“…e cause of deranged liver panel could not be ascertained for 22% (11/50) of the participants and alcoholism and hepatocellular carcinoma (HCC) were responsible for 8% (4/50) and 4% (2/50), respectively, of the cases (Table 1). Viral hepatitis has been associated with deranged liver panel in human studies, thus accounting for the majority of participants [20].…”
Section: Demographics and Aetiology Of Participants Livermentioning
confidence: 99%